APPLICATION OF MATHEMATICAL MODEL WITH GEOINFORMATICS SYSTEM FOR PREDICTION OF LAND USE CHANGE IN PONG NAM RON SUB-WATERSHED KHLONG LAN DISTRIC, KAMPHAENGPHET PROVINCE - Faksomboon, Banchongsak; Suanmali, Wilailak; Chaivino, Nopparat; Khaokham, Pimprapai; Khamcharoen, Nares; Meerod, Siraprapa; Sanyacharernkul, Saksri; Phunlao, Bunchongsri (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This research aimed to study the types and sizes of land use areas including prediction of land use change in Pong Nam Ron Sub-Watershed (PNRSW), Khlong Lan District, Kamphaeng Phet Province by using mathematical model with geoinformatics system. The relationship of the land use data sets is expressed as overlay mapping under the geographical information system approach using IDRISI Taiga program during in 2016, 2020 and 2024. The results showed that PNRSW area was 554.87 square kilometers. The land use classified into 9 types were field crops, paddy fields, urban and built-up land, water bodies, miscellaneous area, forest areas, fruit trees, perennial plants and relational cultivation. The trend of land use area are increasing during in 2020 to 2024 were field crops, urban and built-up land and relational cultivation as 1.40, 0.16 and 0.13 square kilometers or 0.25, 0.03 and 0.02 percentages, respectively. In the other hand, the trend of land use area are decreasing were forest area, perennial plants and miscellaneous areas as 1.54, 0.11 and 0.06 square kilometers or 0.28, 0.02 and 0.01 percentages, respectively because of increasing the land utilization including the tourist attractions are developed and promoted into a new tourist destinations.